Formation and Development of Consumer Properties of Berry Products with Added Nutrition Value - Oksana V.Evdokimova, Maria A.Nikolayeva, Natalya A.Gribova, Lyudmila G.Eliseeva, Lydia V. Berketova, Irina A. Makhotinа (International Journal of Advanced Science and Technology, 2020)
Fruits and berries are widely promoted as healthy foods, being a rich source of antioxidants, vitamins and plant compounds. Therefore, fresh and processed fruit and berry products play an important role in human nutrition; they are part of a diverse group of plant products that vary greatly in energy and nutrient content. The present study is devoted to the influence of osmotic agent type and of its concentration on processing fresh berries with subsequent freezing. Freezing berries without preliminary protection destroys their texture, and during defreezing berries lose their consumer properties and vitamin content. The research is aimed at analyzing the quality of berry products after osmotic dehydration with hypertonic sucrose solution at the given concentration (60°Brix and 70°Brix). The study describes the physical and chemical processes of osmotic dehydration: crystallization temperature; sucrose syrup concentration; changing the mass; frozen moisture amount; water activity; change of the mass fraction of mono-, disaccharides and vitamin C in the berries. As a result, crystallization temperature of dehydrated berries was calculated: from -1.1°C to -2.6°C (60°Brix) and from -1.7°C to -4.8°C (70°Brix). Frozen moisture amount was estimated at 83.2%-92.8% (60°Brix) and 52.2%-87.95% (70°Brix), water activity was 0.9756-0.9891 (60°Brix) and 0.9551-0.9838 (70°Brix). The obtained data allowed determining that the amount of monosaccharides in frozen berries which were preliminarily osmo-dehydrated with 70°Brix sucrose solution rose up to 20%, and the amount of vitamin C to 14.8% (compared with freshly frozen berries). Osmotic dehydration with sucrose solution of specified concentration protects the smooth texture of berries and preserves their organoleptic properties and valuable nutritional composition.